Association between TNF-α promoter polymorphism and Helicobacter pylori cagA subtype infection. Issue 9 (1st September 2001) - Yea, S S; Yang, Y-I; Jang, W H; Lee, Y J; Bae, H-S; Paik, K-H
Abstract : Aims —To assess the importance of tumour necrosis factor α (TNF-α) promoter polymorphism in relation to infection with the cytotoxin associated gene A (cagA) subtype of Helicobacter pylori within a dyspeptic Korean population. Methods —Eighty three patients with gastric disease and 113 healthy controls were studied. The DNA from gastric biopsy specimens was analysed by H pylori specific and cagA specific polymerase chain reaction (PCR). To characterise TNF-α polymorphism at positions −308 and −238, PCR based restriction fragment length polymorphism analysis was performed. Results — Helicobacter pylori infection was closely correlated with G to A transition at position −308 of the TNF-α promoter when compared with healthy controls (odds ratio (OR), 2.912; 95% confidence interval (CI), 1.082 to 7.836; p = 0.034). Although TNF-α −308 polymorphism in patients with H pylori was not significantly different from that in patients without H pylori, the −308A polymorphism was strongly associated with H pylori cagA subtype infection when compared with the polymorphism in cagA negative H pylori infection (OR, 8.757; 95% CI, 1.413 to 54.262; p = 0.019) and healthy controls (OR, 3.683; 95% CI, 1.343 to 10.101; p = 0.011). G to A genetic change at position −238 of the TNF-α gene was not significantly associated with H pylori cagA subtype infection. In addition, genetic polymorphisms at both sites of the TNF-α promoter in patients with H pylori infection did not correlate with the severity of disease. Conclusion —TNF-α −308A polymorphism was significantly related to infection with the H pylori cagA subtype in Korean patients with gastric disease.